Reducing Financial Barriers for Households Due to COVID-19: The Case in India - Grace A. Kabaniha; Praveen Gedam; Henk Bekedam; Indu Bhushan (Taylor & Francis Group, 2021)
As countries all over the world grapple with containing the COVID-19 outbreak, Low- and Middle-Income Countries (LMICs) are particularly hard-pressed because on the one hand, the pandemic has created unforeseen high demand for health services which requires increased spending. On the other hand, the contagion and the public health measures taken to curb it have disrupted economies whilst creating additional spending pressures as well. This constrains the policy options available for LMICs to ensure an adequate and sustainable financing for the health sector's COVID-19 response whilst maintaining routine supply of essential health services. Despite this, as demonstrated by India, many LMICs are undertaking many reform efforts to address both the health and economic hardships caused by the pandemic. In this commentary, we describe the policy tools that one such LMIC, India, has used to enable financing for the outbreak.